Video Modeling to Support Physical Activity in Children with Autism Spectrum Disorder: A Systematic Review - Judge, Joann P.; Morgan, Kristen N.; Clifton, Angela (Journal of the American Academy of Special Education Professionals, 2022)
The purpose of this systematic review was to examine the literature on video modeling to support physical activity in children with autism spectrum disorder (ASD). Specific aims were to (1) identify the targeted skills and behaviors of interest, (2) identify the type of video modeling procedure implemented, and (3) examine the effects of video modeling. This review was guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Search procedures, eligibility criteria, and data extraction were defined a priori to the study protocol. Results indicated the most widely used modeling procedure was basic video modeling. Targeted skills and behaviors included aquatics, dance, motor skills, video gaming, physiological responses, and verbal complimenting. This systematic review found video modeling to be a promising intervention to support physical activity in children with ASD. However, it is suggested for future research to provide even more consistency, clarity, and rigor in the design, implementation, and monitoring of the intervention.